BENEFITS OF USING PHYSICAL EDUCATION MINUTES IN FOREIGN LANGUAGE LESSONS IN SECONDARY SCHOOLS (Uzbek Scholar Journal, 2024)
The article considers pedagogical practice as one of the necessary components of the process of becoming a future teacher. The essence of the concept of "physical training" as a way to study the educational process at school based on the direct participation of trainees in it is revealed. The article highlights and describes some types of physical training at the lessons of pedagogical practice, describes in detail the organization, goals and tasks of each type of pedagogical practice.